If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = x + (-20) -10 = x + -20 Reorder the terms: -10 = -20 + x Solving -10 = -20 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -10 + -1x = -20 + x + -1x Combine like terms: x + -1x = 0 -10 + -1x = -20 + 0 -10 + -1x = -20 Add '10' to each side of the equation. -10 + 10 + -1x = -20 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = -20 + 10 -1x = -20 + 10 Combine like terms: -20 + 10 = -10 -1x = -10 Divide each side by '-1'. x = 10 Simplifying x = 10
| 0-5y=13 | | -8n=-192 | | 3.95+.05(10)= | | -8n=-921 | | 10-3*(4-2)+1=1 | | 4s+s=5 | | 6-5y=13 | | (10-3)*4-2+1=1 | | 3g+7g=20 | | 91=6t-5 | | 4x-3(-2)=-3 | | 10-3*4(-2+1)=1 | | factorn^2+2n+8=8 | | 3n+9=42 | | 5x+17=52 | | 10(-3*4)-2+1=1 | | n^2+2n+8=8 | | 5x+2.3=1.3 | | 5a-(3a-4)= | | -95=5(y+42) | | 9r=4 | | 6x+22=-4x-(2-4x) | | 8(w+90)+20=-12 | | 2+.10x=10 | | 3(x+3)=7(x-2) | | 10-3*4-(2+1)=1 | | 3.95+.05x=10 | | 8(3x-1)=105 | | 6x^2-x^3-16=0 | | 4w+16= | | 3x-19=-7 | | -13-3v=4(8-3v) |